Improvement of Speaking Skills Through Methods Folklore Sociodrama Learning Bugis Batu Cippe - Resky, Resky; Sutrisno, Ahmad Budi; Sarjani Alam, A. Shyam; Ely, Ramli; Primatama Danreng, Ruri Muhammad (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2025)
This study aims to improve students' speaking skills through the application of Bugis folklore-based sociodrama learning methods to fourth-grade students of SDN 18 Tumampua 1. The sociodrama method was chosen to provide students with the opportunity to practice speaking directly through dialogue and roles in real situations reconstructed from regional folklore. This study uses a Classroom Action Research (CAR) design which is implemented in two cycles, which include the planning, implementation, observation, and reflection stages. The research subjects were 29 fourth-grade students. Data collection through observation and speaking performance tests. The results of the study showed an increase in students' speaking skills in each cycle, including aspects of fluency, intonation, vocabulary, expression, and courage to speak in front of the class. In addition, the use of Bugis folklore has been shown to increase students' motivation and self-confidence because the learning material is close to their socio-cultural life. Thus, the application of the Bugis folklore-based sociodrama method is effective in improving students' speaking skills.